Evaluasi Program 100-0-100 di Gampong Lamglumpang Kecamatan Ulee Kareng Banda Aceh - Lia Maisari; Annisa Qadrunnada; Queen Monalisa; Irin Caisarina (Universitas Syiah Kuala, 2022)
The 100-0-100 program is a KOTAKU program to accelerate the prevention and handling of slum settlements. The city of Banda Aceh has targeted 0% slums in 2019, but in reality there are still slum areas. According to the Decree of the Mayor of Banda Aceh Number 422 of 2021, Ulee Kareng Sub-district is the highest sub-district indicated as slum. One of the most densely populated villages in the district is Gampong Lamglumpang. It is important to evaluate the 100-0-100 program in order to ensure that the settlement environment of Gampong Lamglumpang is good and suitable for the community. So this study aims to evaluate the 100-0-100 program that has been implemented by KOTAKU in Lamglumpang Village. The method used in this research is quantitative by using questionnaires and observation. Processing of questionnaire data using excel software by grouping it into three categories, namely good, moderate and not good. The results obtained are that the 100-0-100 program is included in the good group, but based on observations this program has not been run optimally.Keywords: 100-0-100 program, Gampong Lamglumpang, slum